Psychoeducation on Adherence to Treatment of Schizophrenia Patient During Covid-19 Pandemic Era (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: The outbreak of Covid-19 is really disrupting people’s thought and their ability to face theproblem clearly and their mental health could be disturbed.They will go under their circumstance of fear,start to panic, and leads to poor decision making. This fear and anxiety could affect and lead to any negativebehavioural changes of patients to the belief of being infected by avoiding going to the hospital as a sourceof contagion place.Methods: Case study from an inward patient, adult woman that suffered fromschizophrenia for more than10 years and got injection of antipsychotic routinely once a month. During the early time of Covid-19pandemic, the patient and her family are afraid of coming to the hospital to get her injection. After one monthof not getting the injection, she started to relapse again and hospitalized for 10 days.Results: The difficulty faced in handling this case is to provide an understanding of the patient and familyabout adherence on her continuity treatment. Therefore, by giving a psychoeducation using a telemedicineis consideredto the most suitable way to handle this patientto gain more insight about her willingness backto get the monthly treatment during the pandemic situation.
Keywords: Schizophrenia, Covid-19, Adherence of Treatment, Psychoeducation, Telemedicine, Telepsychiatry